Does Schwann cell dedifferentiation originate dermal neurofibromas?. Issue 11 (November 2016) - Iribar, Haizea; Jaka, Ane; Ormaechea, Nerea; Tuneu, Anna; Izeta, Ander; Gutiérrez‐Rivera, Araika
Abstract: Dermal neurofibromas are characteristic of neurofibromatosis type one (NF1), and their developmental origin still unsolved. Although NF1 loss is required for neurofibroma initiation, some features of these benign tumors resemble a skin injury state and cutaneous trauma or other insults might support tumor development. Since adult terminal Schwann cells ensheathing nerve endings are able to dedifferentiate into a progenitor‐like state in response to nerve crushing, we hypothesized that dedifferentiation of NF1 −/− Schwann cells could be at the origin of human dermal neurofibromas. In support of this, here we show that CDH19 (a marker specific of Schwann cell precursors) and Schwann cell dedifferentiation marker SOX2 are significantly upregulated in NF1 tumors. We posit that onset of nerve regeneration might have a role in dermal neurofibroma initiation via dedifferentiation of NF1 −/− Schwann cells.